2014
DOI: 10.1590/0103-8478cr20131015
|View full text |Cite
|
Sign up to set email alerts
|

Viabilidade do sêmen de tatus-peba (Euphractus sexcinctus) centrifugado e diluído em Tris ou agua de coco em pó

Abstract: Viabilidade do sêmen de tatus-peba (Euphractus sexcinctus) centrifugado e diluído em Tris ou agua de coco em pó.Ciência Rural, v.44, n.9, set, 2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…On a recent study developed by our team, we demonstrated that a Tris extender is more effective in maintaining armadillo's sperm viability for 120 min at 34 o C than a coconut water extender (Sousa et al 2014). For this reason, we chose the Tris as the diluting medium for this first attempt on armadillos' sperm freezing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On a recent study developed by our team, we demonstrated that a Tris extender is more effective in maintaining armadillo's sperm viability for 120 min at 34 o C than a coconut water extender (Sousa et al 2014). For this reason, we chose the Tris as the diluting medium for this first attempt on armadillos' sperm freezing.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, an old study had yet revealed that armadillo sperm surface present some difficulties in incorporate fluorescent markers (Bedford & Millar 1978). In this sense, a diluted sample was used as the control for the experiment, once extender promoted the reduction in medium viscosity and allowed the sperm rolleaux dissolution (Sousa et al 2014), thus allowing the interaction among sperm membrane surface and fluorophores. This technique revealed that the mitochondria of the six-banded armadillo's sperm seems to be very sensible to the cryoinjuries, and this statement corroborates to the findings derived from the transmission electron microscopy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation